Closed reduction and percutaneous intramedullary pinning of displaced radial neck fracture in a 12 years old child: reduction technique and outcome - Chandrashekar, Sunil; Laxmansa Katwa, Jagadish; Singh, Amlan (International Journal of Research in Orthopaedics, 2020)
Fracture of the radial neck are uncommon injuries in the pediatric age group. In children, they may present as radial neck fractures, a component of forearm fracture-dislocations, or as isolated fracture-dislocations. Most of the displaced radial neck fractures with more than 300 angulations (Judet type III and IV fractures) should be surgically treated. An unusual variant of radial neck fracture with dislocation of the radial head to the radial side without associated nerve injury. The fracture-dislocation was fixed with closed reduction and Kirschner wire under image intensifier. The patient is being followed up for 6 months. Operative treatment with closed reduction and intramedullary pinning has better correction of angulation and rotation compared to closed reduction techniques with angulation of 300 or more with 100 of rotation. we achieved a supination of 800 and a pronation of 500.